Heroic Legends and Epic - Izadi, Gholam Ali (Journal of History Culture and Art Research, 2017)
In the current study, Romance, as a literary style that has some similar and dissimilar features to epic story, has been compared and contrasted to epic. Some common qualities of romance and epic are: extraordinary plot of events, fictitious story, long story, being preceded by oral narration, express the events that happened in distant past, supernatural cases in story, supporting hero and opposing anti-hero, superstitious and witchery in both of them, the presence of bravery, knighthood and forecasting elements in both. Both stories are based on contrasts or the world is viewed as opposite poles, and characters of both are considered to be “flat”. Epic and romance have dissimilarities. Romance stories are oriented toward love and passion besides the bravery. The top hero of epic is degraded in romance to a lower position. The bravery spirit in romance is reduced and there is a possibility of defeating romance’s hero. However, the hero of epic is undefeatable. The hero of epic pursues greater goals in relation to heroic deeds. The descriptions of the battle are more precise and poetic in epic while romance is incapable of providing exact descriptions of wars. Epic is a source of glory and pride. However, romance is folksier. Therefore, this study investigates the commonalities and the differences between epic and romance.